Legal Protection of Employee Work Agreements with the Contract System Based on Law Number 6 of 2023 (Study of PT Sunwoo Garment Indonesia) - Rizka; Urug Muhammad Hatta (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
The main purpose of this research is to find out how the implementation of the employment agreement between PT Sunwoo Garment Indonesia and its workers is based on Law Number 6 of 2023 and review the extent to which the employment agreement brings welfare to the workers. This research includes a literature study with an empirical juridical method in which primary, secondary, and tertiary legal sources are used. As a result, the employment agreement is an important thing that PT Sunwoo Garment Indonesia pays attention to. The employment contract they have is made based on the applicable legislation. It's just that currently the employment agreement is still based on the old law and has not been updated to follow the new law because it is still waiting for a circular letter from the government. The existing work agreements have generally been able to provide welfare for the workers, such as wage increases every year, compensation, severance pay, benefits, and working leave. However, in terms of reimbursement of working leave, the company has not yet fulfilled it. Even though the workers have felt sufficient with the wages given, the company is still obliged to pay the workers' rights so that workers' welfare can be truly achieved.